2017
DOI: 10.1101/143552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered neocortical gene expression, brain overgrowth and functional over-connectivity inChd8haploinsufficient mice

Abstract: Truncating CHD8 mutations are amongst the highest confidence risk factors for autism spectrum disorders (ASD) identified to date. Here, we report that Chd8 heterozygous mice display subtle brain hyperplasia shortly after birth, hypertelorism, early motor delay, pronounced hypoactivity and anomalous responses to social stimuli. Whereas gene expression in the neocortex is only mildly affected at mid-gestation, over 600 genes are differentially expressed in the early postnatal neocortex. Genes involved in cell ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 68 publications
5
48
2
Order By: Relevance
“…Spontaneous Motor Activity and Reward Learning are Unchanged in Chd8 +/E31T Mice, but These Mice Perform Better than Wild-types at the Rotarod Task There have been conflicting reports of previous lines of Chd8 mice in their spontaneous motor activity in the open field. Some groups have reported hypoactivity in their lines [Jung et al, 2018;Platt et al, 2017;Suetterlin et al, 2018], whereas others have reported no changes in activity [Gompers et al, 2017;Katayama et al, 2016]. Our mice did not display hypoactivity and instead trended toward hyperactivity in the open field, although this difference was not significant (Figure 4(a)).…”
Section: Chd8 +/E31t Mice Do Not Present With Any Anxiety-like Phenotcontrasting
confidence: 63%
See 2 more Smart Citations
“…Spontaneous Motor Activity and Reward Learning are Unchanged in Chd8 +/E31T Mice, but These Mice Perform Better than Wild-types at the Rotarod Task There have been conflicting reports of previous lines of Chd8 mice in their spontaneous motor activity in the open field. Some groups have reported hypoactivity in their lines [Jung et al, 2018;Platt et al, 2017;Suetterlin et al, 2018], whereas others have reported no changes in activity [Gompers et al, 2017;Katayama et al, 2016]. Our mice did not display hypoactivity and instead trended toward hyperactivity in the open field, although this difference was not significant (Figure 4(a)).…”
Section: Chd8 +/E31t Mice Do Not Present With Any Anxiety-like Phenotcontrasting
confidence: 63%
“…The gene structure of Chd8, the location of mutations in mouse models previously generated in the literature [Gompers et al, 2017;Jung et al, 2018;Katayama et al, 2016;Platt et al, 2017 ;Suetterlin et al, 2018], and the targeting vector used for the current study are depicted in Figure 1(a). Consistent with previously published lines, homozygous mutants were embryonic lethal, but heterozygous mutants, which are haploinsufficient for the full-length protein (Figure 1(b)) were used for subsequent behavioral phenotyping.…”
Section: Generation Of Chd8 +/E31t Micementioning
confidence: 99%
See 1 more Smart Citation
“…66,67 Disruption of the homologous gene (Chd8) in animal models has demonstrated that the resulting protein plays a key role in very early neurodevelopmental processes, including neuronal proliferation and differentiation 68,69 as well as cell adhesion and axon guidance. 70 On the other hand, MAGMA competitive gene-set analysis revealed a significant enrichment of discordant genes for functions including synaptic transmission and postsynaptic density, as well as membrane depolarization and voltage-gated cation channel activity. Although these processes have been commonly associated with both schizophrenia 33,35 and cognitive phenotypes, 20,21,24,[71][72][73][74] our study is the first to demonstrate that these synaptic mechanisms operate in a surprising manner: the same synaptic functions that increase risk for schizophrenia also serve to enhance educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a significant number of ASD genes have been shown to play important roles in gene expression regulation, including transcriptional factors, chromatin remodeling factors and other types of epigenetic regulators, such as CHD8, FMR1, MECP2, and so on [Alonso-Gonzalez, Rodriguez-Fontenla, & Carracedo, 2018;De Rubeis et al, 2014]. Accordingly, numerous loss of function animal models were generated, especially the mouse models, to recapitulate the disease phenotypes and to explore the underlying molecular mechanisms [Araujo et al, 2017;Arbogast et al, 2018;Caubit et al, 2016;Celen et al, 2017;Cheng et al, 2018;Gabel et al, 2015;Harrington et al, 2016;Huang et al, 2018;Jung et al, 2018;Kong et al, 2014;McGill et al, 2018;Prilutsky et al, 2015;Provenzano et al, 2016;Raman et al, 2018;Scandaglia et al, 2017;Sgado et al, 2013;Suetterlin et al, 2018;Zhao, Goffin, Johnson, & Zhou, 2013]. With these models, RNA-Seq or microarray experiments have been performed in various brain regions to identify the downstream targets of the corresponding ASD genes.…”
Section: Introductionmentioning
confidence: 99%